1968
DOI: 10.1136/thx.23.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve replacement: Long-term results, with particular reference to changes in pulmonary vascular resistance

Abstract: , were reviewed from one to three years after operation. These patients had presented with serious mitral valve disease and there was a high incidence of severe dyspnoea and persistent congestive failure before operation. There were four operative deaths, and two survivors had poor results due to regurgitation alongside the prosthesis. The remaining 10 patients showed considerable improvement. Although no diuretics were given after operation there was little dyspnoea and congestive failure resolved. Anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Publications in the earlier days of bypass surgery had shown that the overall surgical mortality for mitral valve surgery had been higher in this group of patients (Nichols et al, 1964;Hamer et al, 1968). The present survey of mitral valve operations in a fouryear period has revealed that, despite the findings of severe pulmonary hypertension and a high pulmonary vascular resistance in 56 patients, the hospital mortality of 5-4% was the same as in a group of 336 consecutive patients whose pulmonary artery systolic pressure was less than 70 mmHg.…”
Section: Discussionmentioning
confidence: 94%
“…Publications in the earlier days of bypass surgery had shown that the overall surgical mortality for mitral valve surgery had been higher in this group of patients (Nichols et al, 1964;Hamer et al, 1968). The present survey of mitral valve operations in a fouryear period has revealed that, despite the findings of severe pulmonary hypertension and a high pulmonary vascular resistance in 56 patients, the hospital mortality of 5-4% was the same as in a group of 336 consecutive patients whose pulmonary artery systolic pressure was less than 70 mmHg.…”
Section: Discussionmentioning
confidence: 94%
“…Although pulmonary vascular resistance is regarded as a useful index of severity of pulmonary hypertension, its validity has been questioned (Rudolph and Nadas, 1962) and its interpretation may be difficult (Fritts and Cournand, 1959;Braunwald, Braunwald, and Morrow, 1962). Hamer et al (1968) suggested that higher values of PVR do not necessarily indicate more severe disease of the pulmonary vasculature. The concept of PVR may be valid for steady flow situations where the resistance varies with the pressure difference across the circuit, but higher values of PVR may be related to low cardiac output as well as to an increase in PAm-LAm (Hollinrake, Baidya, and Yacoub, 1973).…”
Section: Resultsmentioning
confidence: 99%
“…With progression of disease, PVR also increases due to reactive pulmonary vasoconstriction and organic changes in the pulmonary microvasculature. The presence of severe PAH not only has an influence on the prognosis of mitral valve disease, it also affects the postoperative outcome as borne by several studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Some authors have shown that severe PAH regresses after MVR/mitral valve repair [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of severe PAH not only has an influence on the prognosis of mitral valve disease, it also affects the postoperative outcome as borne by several studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Some authors have shown that severe PAH regresses after MVR/mitral valve repair [4][5][6][7][8][9][10][11][12][13][14][15]. However, others have shown that severe PAH is associated with higher postoperative mortality especially in patients with supra-systemic PA pressures [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%